MANAGERIAL SUPERVISION OF MADRASAH ALIYAH IN MUARO JAMBI: INSIGHTS FROM PRINCIPALS AND SUPERVISORS - Sari, Nori Nopita (Darul Ilmi Bina Insan Foundation, 2024)
Madrasah supervisors play a critical role in enhancing the quality of madrasah education, as emphasized by the Regulation of the Minister of Religion. These regulations outline the duties and functions of supervisors, requiring them to demonstrate core competencies in three key areas: academic supervision, educational evaluation, and research and development. The purpose of this study was to determine the perception of the Madrasah principal regarding the planning of the supervisor's managerial supervision program, and to determine the perception of the Madrasah principal regarding the implementation of the supervisor's managerial supervision program for Madrasah Aliyah in Muaro Jambi Regency regarding the performance of his own supervisor, namely under the command of Mr. Alimuddin as the elected Supervisors' Working Group (Pojakwas) until 2024. This study uses a qualitative research method, by providing a comprehensive picture of reality regarding the perception of the madrasah principal regarding the performance of the managerial supervision of the supervisor of State Madrasah Aliyah in Muaro Jambi Regency with a case study approach to find out about activities at certain times and places by looking at their own experiences. The results of the study indicate that Madrasah Supervisors in Muaro Jambi Regency play an important role in improving the quality of education in various madrasahs through supervision and monitoring activities.